2017
DOI: 10.1111/1365-2745.12768
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between rainfall, fire and herbivory drive resprouter vital rates in a semi‐arid ecosystem

Abstract: Summary Global change is threatening ecosystems and biodiversity world‐wide, creating a pressing need to understand how climate and disturbance regimes interact and influence the persistence of species. We quantify how three ecosystem drivers – rainfall, fire and herbivory – influence vital rates in the perennial resprouting graminoid, Triodia scariosa, a foundation species of semi‐arid Australia. We used an 11‐year dataset from a fire and herbivore exclosure experiment, to model flowering, post‐fire recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 69 publications
0
39
1
Order By: Relevance
“…, Giljohann et al. ). In our study, high‐severity fire plots had the lowest soil moisture and almost no seedling recruitment, while low‐severity fire plots had the highest soil moisture (Appendix ), and the greatest seedling recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Giljohann et al. ). In our study, high‐severity fire plots had the lowest soil moisture and almost no seedling recruitment, while low‐severity fire plots had the highest soil moisture (Appendix ), and the greatest seedling recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…, Giljohann et al. ). Further, despite the ecological significance of the understory (Gilliam ), modeling of temperate forest dynamics rarely incorporates this stratum (Landuyt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Amazon forests by Massad et al . and semiarid sand dunes in Australia by Giljohann et al . showed that overall herbivory was higher following fires for a variety of plant species.…”
Section: Other Case Studies Of Food Webs Impacted By Disturbancesmentioning
confidence: 99%
“…found that adding nutrients to burned plots increased herbivory. Giljohann et al . found that fire increased herbivory in dry years but not wet years.…”
Section: Other Case Studies Of Food Webs Impacted By Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation